The Expression Patterns and Roles of Lysyl Oxidases in Aortic Dissection - Yi, Xin; Zhou, Yi; Chen, Yue; Feng, Xin; Liu, Chang; Jiang, Ding-Sheng; Geng, Jing; Li, Xiaoyan; Jiang, Xuejun; Fang, Ze-Min (Frontiers in Cardiovascular Medicine, 2021)
Background: Lysyl oxidases (LOXs), including LOX, LOXL1, LOXL2, LOXL3, and LOXL4, catalyze the formation of a cross-link between elastin (ELN) and collagen. Multiple LOX mutations have been shown to be associated with the occurrence of aortic dissection (AD) in humans, and LOX-knockout mice died during the perinatal period due to aortic aneurysm and rupture. However, the expression levels and roles of other LOX members in AD remain unknown. Methods: A total of 33 aorta samples of AD and 15 normal aorta were collected for LOXs mRNA and protein levels detection. We also analyzed the datasets of AD in GEO database through bioinformatics methods. LOXL2 and LOXL3 were knocked down in primary cultured human aortic smooth muscle cells (HASMCs) via lentivirus. Results: Here, we show that the protein levels of LOXL2 and LOXL3 are upregulated, while LOXL4 is downregulated in AD subjects compared with non-AD subjects, but comparable protein levels of LOX and LOXL1 are detected. Knockdown of LOXL2 suppressed MMP2 expression, the phosphorylation of AKT (p-AKT) and S6 (p-S6), but increased the mono-, di-, tri-methylation of H3K4 (H3K4me1/2/3), H3K9me3, and p-P38 levels in HASMCs. These results indicate that LOXL2 is involved in regulation of the extracellular matrix (ECM) in HASMCs. In contrast, LOXL3 knockdown inhibited PCNA and cyclin D1, suppressing HASMC proliferation. Our results suggest that in addition to LOX, LOXL2 and LOXL3 are involved in the pathological process of AD by regulating ECM and the proliferation of HASMCs, respectively. Furthermore, we found that LOXL2 and LOXL4 was inhibited by metformin and losartan in HASMCs, which indicated that LOXL2 and LOXL4 are the potential targets that involved in the therapeutic effects of metformin and losartan on aortic or aneurysm expansion. Conclusions: Thus, differential regulation of LOXs might be a novel strategy to prevent or treat AD.